Shared and Distinct Functions of Type I and Type III Interferons - Lazear, Helen M.; Schoggins, John W.; Diamond, Michael S. (Immunity (Cambridge, Mass.), 2019)
Type I interferons (IFNs) (IFN-α, IFN-β) and type III IFNs (IFN-λ) share many properties, including induction by viral infection, activation of shared signaling pathways, and transcriptional programs. However, recent discoveries have revealed context-specific functional differences. Here, we provide a comprehensive review of type I and type III IFN activities, highlighting shared and distinct features from molecular mechanisms through physiological responses. Beyond discussing canonical antiviral functions, we consider the adaptive immune priming, anti-tumor, and autoimmune functions of IFNs. We discuss a model wherein type III IFNs serve as a front-line defense that controls infection at epithelial barriers while minimizing damaging inflammatory responses, reserving the more potent type I IFN response for when local responses are insufficient. In this context, we discuss current therapeutic applications targeting these cytokine pathways and highlight gaps in understanding of the biology of type I and type III IFNs in health and disease. Lazear, Schoggins, and Diamond review the shared and distinct features of type I and III interferons, from molecular mechanisms through physiological responses. In this context, they discuss the current state of interferon-based therapeutic approaches in the clinic and highlight gaps in understanding of the biology of these cytokines.